Dampak Penggunaan Sistem Informasi Manajemen Terhadap Kinerja Pengawai DPUPR Kabupaten Padang Pariaman - ive, arivetullatif; Junaidi, Junaidi (CV. ITTC INDONESIA, 2024)
The advent of information technology has significantly impacted organizational performance by leveraging management information systems to address existing challenges. Notably, employee performance decline poses a substantial issue. Organizations lacking management information systems exhibit diminished employee performance, potentially leading to deviations and dissatisfaction. This study employed saturated sampling with 60 respondents and questionnaire distribution. SPSS-based data analysis revealed a statistically significant relationship between management information systems (X) and employee performance (Y), with Sig. < 0.05 (Sig. 0.00 < 0.05). The findings underscore the pivotal role of management information systems in enhancing employee performance.